Screening for Chronic Kidney Disease in Patients with Non-Communicable Chronic Diseases in Primary Health Care - Suzana do Ceu Silva Rodrigues Costa; Rosenilda Rodrigues dos Santos; Maria das Graças Venâncio; Gizely Rhose de Sousa; José Roberval Ferreira de Oliveira; Josefa Soares Cavalcante; Sérgio Raimundo Ernesto Machado; Dênis Carvalho Soares Cavalcante; Jocilane Lima de Almeida Vasconcelos (RSV, 2026)
Chronic kidney disease (CKD) is one of the fastest-growing non-communicable diseases worldwide and has become an important contributor to morbidity, mortality, and healthcare expenditure. Because the disease progresses silently during its early stages, many individuals remain undiagnosed until significant and often irreversible renal damage has occurred. Diabetes mellitus, hypertension, obesity, and cardiovascular disease represent the principal risk factors for CKD, making patients with non-communicable chronic diseases a priority population for systematic screening. Early identification of kidney dysfunction allows timely interventions that may slow disease progression, reduce cardiovascular complications, improve quality of life, and decrease the need for renal replacement therapy. For this reason, Primary Health Care has become the most appropriate setting for implementing organized screening strategies due to its accessibility, continuity of care, and long-term management of chronic conditions. This academic essay examines the importance of screening for chronic kidney disease among individuals living with non-communicable chronic diseases within Primary Health Care. The discussion explores the epidemiological relevance of CKD, the rationale for systematic screening, current diagnostic approaches, organizational barriers, and the contribution of primary healthcare teams to early detection and disease management. The analysis emphasizes that integrating kidney health into routine chronic disease care represents an essential strategy for improving clinical outcomes while promoting more efficient and sustainable healthcare systems.